Profiling of Islamic calligraphy scripts used for architectural dcoration of masjid in peninsular Malaysia - Kamaruddin, Zumahiran; Baydoun, Ziad; Nik Mahidin, Nik Ahmed Mazlan (Malaysian Institute of Planners, 2020)
In Malaysia, the introduction of the Islamic calligraphy, especially after the spread of Islam in the 14th century has impacted on the further development of decorative art in the built environment. While Islamic calligraphy has witnessed significant developments in the past decades, it still lacks a profiling classification system of calligraphy scripts that give impact to the contemporary mosque. The objectives of the study are to analyse the visual qualities of the calligraphy scripts in the mosque components and its compositional categories and to determine the relationship between the calligraphy placement and the mosque architecture within the interior and exterior fabrics of the buildings. This research involved an analytical review of the Islamic calligraphy found in the 10 selected mosques in Selangor and Kuala Lumpur, Malaysia and their depiction in various components. Face-to-face interviews with the mosque authorities and local calligraphers on the types and styles of scripts used in the mosque components were conducted as a complementary measure to the analytical method. The analysis reveals the application of cursive and angular style of scripts, fabricated in specified shapes, sizes and dimensions of the mosque components. Selection and depiction of calligraphy, especially in Thuluth and Kufi scripts suggest their strong preference to the traditional major styles ranging from its composition to the determination of its positional layout regardless of differences in the mosque architecture style.